Предмет: Математика,
автор: aipeee868w9
раскрой скобки и упростите выражение -9(3-a)+3(-3a-3)-7(-9+a) ПРОШУ быстрее
Ответы
Автор ответа:
0
Ответ:
Пошаговое объяснение:
-9 * (3 - a) + 3 * (-3a - 3) - 7 * (-9 + a) = -27 + 9а - 9а - 9 + 63 - 7а = 27 - 7а
Автор ответа:
0
Ответ:-27+9a-9a-9+63-7a=-36+63-7a=27-7a
Пошаговое объяснение:
Похожие вопросы
Предмет: Английский язык,
автор: Polinka1203
Предмет: Английский язык,
автор: madamane4ka
Предмет: Русский язык,
автор: vikadocent
Предмет: Математика,
автор: Юлязайка134
Предмет: Математика,
автор: саша3642